Eurasian Union: Instruments of Management and Integration - Yu. V. Sablina (Управленческое консультирование)
The aim of the study: to study the features of management tools and integration of the EAEU at the present stage of its existence. Research methods: problem-theoretical, chronological, systemic, historical-comparative. Results: proposals to improve the existing management and integration tools of the EAEU have been developed. Conclusions: at this stage of development, the management and integration tools within the Eurasian Union are quite efcient, but due to changes in the world, both political and socio-economic and technological, innovations and improvements in this regard are possible, which can increase the efciency of the EAEU functioning.